Effectiveness of Adding Strengthening Lower Extremity Exercise on Gait Speed of Hajj Pilgrims Who Receive Walking Aerobic Exercises - Rahmi Isma Asmara Putri; Dian Permata; Naela Munawaroh (Jurnal Kedokteran Diponegoro, 2024)
Background: In the Hajj pilgrimage, the daily activities of Hajj Pilgrims also require good walking skills. Walking is the most common physical activities. Individuals with limited mobility have been found to have greater energy costs related to daily life tasks. Resistance training is a type of exercise that can increase muscular speed, power, strength, hypertrophy, and coordination. The decreased muscle strength leads to decrease in walking ability. Objective: Researchers want to compare that adding strengthening lower extremity exercise can improve the gait speed on Hajj Pilgrims more than control group who receive walking aerobic exercise only. Methods: A randomized controlled trial was used for this research. There were 36 participants divided into an 18-person intervention group and an 18-person control group. The groups received walking aerobic exercises five times a week and the intervention group were added strengthening lower extremity exercise twice a week. A 4-meter gait speed test was used to evaluate gait speed both pre- and post- a six-week course of intervention. Results: After six weeks, there was a significant increase in gait speed in both the intervention group (p=0.000) and the control group (p=0.000). There’s no significant difference between the interventions of each group (0.86 ± 0.58) compared to the control group. (0.87 ± 0.66) (p=0.968). Conclusion: Walking aerobic exercise and adding strengthening lower extremity exercise can increase gait speed significantly. However, walking aerobic exercise with or without strengthening lower extremity exercise addition there is an increase in gait speed.